Hyperreactio leuteinalis: benign tumour associated with pregnancy mimicking ovarian malignancy - Tarannum, Nazli; Akhtar, Nishat (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Hyperreactio leuteinalis refers to pregnancy related enlargement of B/L ovaries rarely unilateral ovary, moderate to marked size due to multiple theca leutein cysts. It is a rare finding associated with pregnancy seen commonly in multiple gestation, GTDs and fetal abnormalities: viz hydrops. It is caused by elevated B-hcg level. We report a case of 28 years old female, primi with 13 spontaneously conceived weeks pregnancy who presented to ANC OPD for regular check-up and vague abdominal discomfort. USG revealed a large right sided ovarian mass, solid cystic in appearance pushing the uterus to left side and upwards. Staging laparotomy was done at 14 weeks viewing it to be a malignant mass. Unilateral right sided oophorectomy was done along with biopsy taken from left ovary. On microscopic histological examination diagnosis of hyperreactio leuteinalis unilateral ovary was made. Hyperreactio leuteinalis mimicking ovarian malignancy on USG results in unnecessary surgical intervention.